2014
DOI: 10.1007/s10592-014-0628-6
|View full text |Cite
|
Sign up to set email alerts
|

No reduction in genetic diversity of Swiss stone pine (Pinus cembra L.) in Tatra Mountains despite high fragmentation and small population size

Abstract: In Europe, most of the alpine timberline ecotone has been altered by human activities and climate change. Hence, mountain forests are of the highest conservation interest. Here, we screened 25 populations of Swiss stone pine (Pinus cembra L.) from the Carpathians and the Alps, using a set of ten microsatellite primers to assess the relative conservation value of populations sampled in Polish and Slovak Tatra National Parks, where potential extinction risk is the highest within the Carpathian range. Although en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
2
15
1
1
Order By: Relevance
“…Our results show that gene flow through pollen should be generally sufficient to counterbalance genetic drift. In fact, studying genetic structure of P. cembra in the Tatras, we detected very weak genetic differentiation (Dzialuk et al 2014), suggesting that gene exchange between subpopulations is probably high. On the other hand, based on mating system parameters, we argued that small and isolated subpopulations of P. cembra both in the Alps and Carpathians can experience severe local pollen limitation, which can dramatically lower seed production (Salzer and Gugerli 2012) and fitness of individuals due to inbreeding.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Our results show that gene flow through pollen should be generally sufficient to counterbalance genetic drift. In fact, studying genetic structure of P. cembra in the Tatras, we detected very weak genetic differentiation (Dzialuk et al 2014), suggesting that gene exchange between subpopulations is probably high. On the other hand, based on mating system parameters, we argued that small and isolated subpopulations of P. cembra both in the Alps and Carpathians can experience severe local pollen limitation, which can dramatically lower seed production (Salzer and Gugerli 2012) and fitness of individuals due to inbreeding.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the latter is assumed to result entirely from pollen dispersal and not population genetic structure (Austerlitz and Smouse 2001). The absence of correlation between genetic and geographic distance found in the Tatras (Dzialuk et al 2014) suggests that the observed pollen structure was indeed a result of limited pollen dispersal. Nonetheless, due to discontinuous sampling (see Fig.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations